Endocalidad educativa como apropiación social de los hechos pedagógicos: Educational Endocality as Social Appropriation of Pedagogical Facts - Landeo-Quispe, Alex-Sandro; Orihuela Rojas, Vladimir; Orihuela Rojas, Fernando Pool (Universidad del Zulia, 2021)
The research analyzes the epistemic foundations of endo-quality as a quality of the best educational forms, by allowing the social appropriation of pedagogical facts. Along with this, the teaching vocation stands out as a demonstration of solidarity towards the communities. The use of education as a tool that provokes coexistence is the possibility of ethically coordinated societies. These strategies limit the fragmentations caused by behavioral, positivist and utilitarian educational models. In this sense, a case study of university graduates in the city of Huancayo, Peru is carried out. Inquiries coordinate bibliographic examinations along with observations; they consider descriptive and experiential approaches.